Zygomycosis due to Mucor racemosus Associated with a Circovirus Infection in a Blue Tit (Cyanistes caeruleus). (November 2018) - Schmitz, A.; Korbel, R.; Rinder, M.
Summary: In spring 2014, several wild passeriform garden birds were found severely ill or dead, all with severe periocular swellings. A blue tit ( Cyanistes caeruleus ) showing severe depression was humanely destroyed and sent for necropsy examination. In this bird, the lower eyelids were sagging, red and oedematous. Microscopical examination revealed marked infiltration of the eyelid tissue with fungal hyphae (stained by periodic acid–Schiff) without any inflammatory reaction. Polymerase chain reaction followed by sequencing identified Mucor racemosus and a so far unknown circovirus. The circovirus infection in this bird might have induced immunosuppression and thus facilitated the fungal infection. To our knowledge this is the first report of ocular M. racemosus infection associated with circovirus infection in a bird.